The Role Of School Libraries In Fostering Student Literacy In The Center Of Indonesian Citiez Education Klang, Selangor, Malaysia - Yuliana, Yuanita; Laksana, Sigit Dwi; Sumaryanti, Lilis (Program Studi PGMI, 2025)
Reading is a process of absorbing knowledge through writing and reading which is available in various online and offline media. Each student definitely has different abilities, from fast, medium, and even slow in capturing knowledge from what they have read. This research activity aims to increase students' interest in reading, with the existence of a library in this school institution, it is hoped that students will be able to increase their reading interest in comfortable conditions and can increase their knowledge for future preparation. The objects of this research are teachers and all students at the Indonesian Citizen Education Center (at PPWNI) Klang using data collection techniques through observation and interviews using descriptive qualitative methods in the form of words or writing. From the data obtained, it shows the first Not all students at PPWNI Klang like to read in the library. Second, the books that students read are regional story books.